Curative resection of carcinoma of the ampulla of Vater with lymph node metastases around the abdominal aorta after chemotherapy: A case report. (2016) - Fujii, Wataru; Hayashi, Ken; Yamada, Shigetoshi; Kusanagi, Hiroshi
Highlights: Curative resection of carcinoma with lymphnode metastasis around the aorta. Conversion surgical strategy for unresectable case after chemotherapy. Rare case of biliary tract cancer with distant metastasis. Abstract: Introduction: For carcinoma of the ampulla of Vater, lymph node metastasis around the abdominal aorta is an inoperable factor equivalent to distant metastasis, such as hepatic metastasis or peritoneal carcinomatosis, making the cancer unresectable. Presentation of case: A 53-year-old man was referred to our hospital and was diagnosed as having carcinoma of the ampulla of Vater with lymph node metastases around the abdominal aorta. Although only chemotherapy was initially scheduled, the chemotherapy was effective, and the metastases were dramatically reduced after 4 cycles of chemotherapy. Curative surgical resection was performed. Discussion: There were only eight case reports describing curative resections of initially unresectable biliary tract carcinomas excluding intrahepatic cholangiocellular carcinoma after chemotherapy. Conclusion: Curative surgical resection after chemotherapy may be a feasible treatment plan in patients with unresectable biliary tract cancer.